1999
DOI: 10.1089/107999099313613
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Monocyte Chemokine Production and Nuclear Factor Kappa B Activity by Oxidants

Abstract: Reactive oxygen species can directly damage tissue. In this setting, amplification of tissue damage also occurs through infiltration of inflammatory cells either acutely or chronically. Several recent studies suggest that reactive oxygen species stimulate production of certain chemokines, which are potent chemoattractants for inflammatory cells. In the present study, we examined whether oxidants, generated by the combination of xanthine and xanthine oxidase (X/XO), alter chemokine production by monocytes and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For example, a short burst of NO augments the activation of NF-B in LPS or TNF-␣stimulated cells [176,177], and other studies show that longer duration of NO exposure led to inhibition and served as a negative-feedback signal [178 -180]. Other observations with ROS show that low levels of H 2 O 2 can similarly enhance NF-B activity [181,182], and higher H 2 O 2 (Ͼ100 M) inhibited its activity [178 -180]. These redox-mediated inhibitory reactions involve critical cysteine thiolates necessary for DNA binding [183][184][185].…”
Section: No and Proinflammatory Genesmentioning
confidence: 99%
“…For example, a short burst of NO augments the activation of NF-B in LPS or TNF-␣stimulated cells [176,177], and other studies show that longer duration of NO exposure led to inhibition and served as a negative-feedback signal [178 -180]. Other observations with ROS show that low levels of H 2 O 2 can similarly enhance NF-B activity [181,182], and higher H 2 O 2 (Ͼ100 M) inhibited its activity [178 -180]. These redox-mediated inhibitory reactions involve critical cysteine thiolates necessary for DNA binding [183][184][185].…”
Section: No and Proinflammatory Genesmentioning
confidence: 99%
“…Studies have shown that in the setting of fatty liver, the severity of oxidative injury depends upon the degree of unsaturation of cellular lipids (60,61). High levels of unsaturation amplify oxidative insults, leading to enhanced lipid peroxidation and downstream consequences such as chemokine production (62)(63)(64). In our experiments, the substantial LPS-induced rise in TBARS that occurred in Mttp ⌬/⌬ mice relative to control mice is likely due to their disproportionate stores of linoleic acid, an essential polyunsaturated fatty acid.…”
Section: Mttpmentioning
confidence: 99%
“…17,18 Similarly, generation of ROIs with xanthine/ xanthine oxidase induced IL-8 and MCP-1 production from monocytes, but not U937 cells, and this induction is associated with increased NF-B DNA binding. 20 Thus the potential for a role of ROIs in induction of MCP-1 in venular endothelium was considered.…”
mentioning
confidence: 99%